Potential targeted therapy based on deep insight into the relationship between the pulmonary microbiota and immune regulation in lung fibrosis - Zhang, Tao; Zhang, Min; Yang, Liqing; Gao, Lingyun; Sun, Wei (Frontiers in Immunology, 2023)
Pulmonary fibrosis is an irreversible disease, and its mechanism is unclear. The lung is a vital organ connecting the respiratory tract and the outside world. The changes in lung microecology affect the progress of lung fibrosis. The latest research showed that lung microecology differs in healthy people, including idiopathic pulmonary fibrosis (IPF) and acute exacerbation-idiopathic pulmonary fibrosis (AE-IPF). How to regulate the lung microecology and whether the potential regulatory mechanism can become a necessary targeted treatment of IPF are unclear. Some studies showed that immune response and lung microecology balance and maintain lung homeostasis. However, unbalanced lung homeostasis stimulates the immune response. The subsequent biological effects are closely related to lung fibrosis. Core fucosylation (CF), a significant protein functional modification, affects the lung microenvironment. CF regulates immune protein modifications by regulating key inflammatory factors and signaling pathways generated after immune response. The treatment of immune regulation, such as antibiotic treatment, vitamin D supplementation, and exosome micro-RNAs, have achieved an initial effect in clearing the inflammatory storm induced by an immune response. Based on the above, the highlight of this review is clarifying the relationship between pulmonary microecology and immune regulation and identifying the correlation between the two, the impact on pulmonary fibrosis, and potential therapeutic targets.